2021
DOI: 10.1177/20563051211036939
|View full text |Cite
|
Sign up to set email alerts
|

Politics and Politeness: Analysis of Incivility on Twitter During the 2020 Democratic Presidential Primary

Abstract: In the past decade, social networking sites have become central forums for public discourse and political engagement. Of particular interest is the role that Twitter plays in the facilitation of political discourse. To this end, the existing literature argues that a healthy political discussion space is key to maintaining a trusting and robust democratic society. Using Suler’s online disinhibition effect as a theoretical orientation, this study seeks to address the extent of incivility on Twitter in discourse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Another study analyzing 18 million tweets surrounding political candidates in America revealed associations between certain candidates and incivility discourse, with specific policy issues closely linked to uncivil discourse. Linking these results through k-means clustering, the study illustrates that gun control and immigration are closely related to mentions of controversial candidates [28]. Other research indicates there is an important distinction to make here; impoliteness is directed at individuals, while incivility is predominantly driven by the topic.…”
Section: Topic-driven Toxicitymentioning
confidence: 78%
See 1 more Smart Citation
“…Another study analyzing 18 million tweets surrounding political candidates in America revealed associations between certain candidates and incivility discourse, with specific policy issues closely linked to uncivil discourse. Linking these results through k-means clustering, the study illustrates that gun control and immigration are closely related to mentions of controversial candidates [28]. Other research indicates there is an important distinction to make here; impoliteness is directed at individuals, while incivility is predominantly driven by the topic.…”
Section: Topic-driven Toxicitymentioning
confidence: 78%
“…In reality, civility, a fundamental norm for deliberative discourse, is frequently violated in online discussions, transforming platforms into areas rife with frustration, hate, and incivility, often displayed through insults and flaming. The escalating concern about online incivility is evident among the American public, with 68% identifying it as a "major problem" and nearly 90% recognizing its severe consequences, encompassing cyberbullying, harassment, violence, hate crimes, intimidation, threats, intolerance, and a diminished sense of safety in public spaces [27,28]. Several scholars underscore that incivility, rather than civility, prevails in online conversations, despite the potential for political discussion on social media [26,29,30].…”
Section: The Lost Promise Of Online Deliberationmentioning
confidence: 99%
“…Tweets in this cluster relied heavily upon hashtags to demonstrate their support for Bernie and his platform of signature issues; signaling support by writing, “#MedicareForAll,” “#BernieBeatsTrump.” “#Bernie2020,” “#NotMeUs” which was followed or preceded by the message of “Vote for Bernie.” Hashtags symbolically convey a person’s stance and are a mechanism for advocating for one’s position [ 76 ]. We coded this cluster as ‘moderate because most of the hashtags passively named issues or endorsement of Bernie, thereby upholding civility in discussions of politics [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of discourses surrounding hashtags on Twitter has been applied across various disciplines and for diverse purposes, such as sustainability discourses [46,47], political discourses [48,49] or health and nutrition discourses [45,50,51]. These studies have demonstrated that Twitter data are valuable for gaining insights into perspectives that are often challenging to access and underrepresented in empirical social research.…”
Section: Social Media As a Voice Amplifier For Food Poverty Experiencesmentioning
confidence: 99%